(untitled) (Mahadi: Indonesia Journal of Law, 2023)
The achievement of basic rights related to adequate housing is one of the goals of Indonesia’s full commitment to realizing sustainable development. This study aims to harmonize regulations regarding reasonable agreements and actions to achieve fitness for sustainable development goals. This study will concentrate on examining the harmonization of the actual contents of regulations by using a concept approach and legal methods, taking into account the importance of relevant laws to support these development goals. Defining what constitutes a viable and sustainable organization is the first step in the discussion. The next section provides an overview of how the definition of "decent and sustainable housing" is used to form the substance of laws and regulations related to adequate housing. These definitions have been established. In accordance with SDGs Goal 11, the substance of legislation related to adequate housing is determined by the research findings that can be produced.